2009
DOI: 10.1016/j.cellbi.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐adipocytes commitment to neurogenesis 1: Preliminary localisation of cholinergic molecules

Abstract: A great effort has recently been made to obtain human stem cells able to differentiate into cholinergic neurons, as a number of diseases are associated to the cholinergic neuron loss, degeneration or incorrect function (Alzheimer's disease and motor neuron disease). A stem cell population (i.e. pre-adipocytes) is present in the adipose stromal compartment. Pre-adipocytes, like the mesodermic derivative cells, retain high plasticity and potentiality to convert in vitro from one phenotype into many others, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Additionally, when transplanted into a SCID mouse model, the transplanted cells expressed albumin in vivo. When proper induction cues are applied in vitro, ASCs display neuronal and/or oligodendrocytic markers [16,[136][137][138]. ASCs take on a bipolar morphology, similar to that of neuronal cells, while expressing neuronal associated proteins such as nestin, intermediate filament M, Neu N, as well as glial fibrillary acidic protein (GFAP), a protein associated with oligodendrocyte differentiation.…”
Section: Asc Differentiation Potentialmentioning
confidence: 98%
“…Additionally, when transplanted into a SCID mouse model, the transplanted cells expressed albumin in vivo. When proper induction cues are applied in vitro, ASCs display neuronal and/or oligodendrocytic markers [16,[136][137][138]. ASCs take on a bipolar morphology, similar to that of neuronal cells, while expressing neuronal associated proteins such as nestin, intermediate filament M, Neu N, as well as glial fibrillary acidic protein (GFAP), a protein associated with oligodendrocyte differentiation.…”
Section: Asc Differentiation Potentialmentioning
confidence: 98%
“…Since ASCs are of mesodermal origin, they can differentiate into the adipogenic, osteogenic, and chondrogenic lineages, and even the myogenic lineage, leading to skeletal muscle, smooth muscle, and cardiomyocytes [41], [42], [47], [48]. Interestingly, however, ASCs have also been shown to possess the potential to differentiate into cells of the ectodermal and endodermal lineages, such as neuron-like cells, endothelial cells, epithelial cells, hepatocytes, pancreatic cells, and hematopoietic supporting cells [49], [50], [51], [52], [53], [54], [55], [56], [57].…”
Section: Adipose-derived Stem Cells (Ascs)mentioning
confidence: 99%
“…Fat is an active and dynamic tissue composed of several different cell types, including adipocytes, fibroblasts, smooth muscle cells, endothelial cells, and adipogenic progenitor cells called pre-adipocytes [30], [31], [32]. Stem cells isolated from lipoaspirates have demonstrated a broad in vitro adipogenic, chondrogenic, osteogenic, and myogenic lineage commitment [33], [34] as well as differentiation into pancreatic cells, hepatocytes, and neurogenic cells [35], [36], [37]. Cytometric analysis of adipose-derived stem cells (ASCs) has shown that these cells do not express CD31 and CD45, but do express CD34, CD73, CD105, and the mesenchymal stem cell marker CD90 [38], [39].…”
Section: Efficacy Of Lipofillingmentioning
confidence: 99%